PEMANFAATAN KOTORAN SAPI DAN SAMPAH SAYUR PADA PEMBUATAN BIOGAS DENGAN FERMENTASI SAMPAH SAYURAN - Fitri, Medya Ayunda; Dhaniswara, Trisna Kumala (Journal of Research and Technology, 2018)
Biogas is one solution to the use organic waste (livestock manure and vegetables). The aim of the research was to find out the effectiveness of livestock manure and fermentation of vegetable waste into biogas. This research was carried out using fermented vegetable waste for 10-12 days, then it was chopped and blended. The vegetable waste is then mixed with cow dung and water according to the determined variables. The mixture was put into a brown glass bottle and the bottle mouth was closed with a balloon and deposited for 8 days. Furthermore, the CO2 gas produced wasreleased and start to deposite again for 20-30 days. Trapped methane gas obtained from in the balloon was then stored to measure the produced volume and pH and also the methane gas. The results obtained from the research that is were the best pH obtained from vegetable waste blender fermentation treatment (% water100 and the percentage ofKS: SO was 75:25) was 7 and the largest volume was obtained from fermented chopped vegetable waste treatment (water% 300 and percentage KS: SO was 100: 0) of 78.73 cm3. Keywords: Biogas, Fermentation of Vegetable Waste, Cow Manure.